Fibrosis status, extrahepatic multimorbidity and all-cause mortality in 53,093 women and 74,377 men with metabolic dysfunction associated steatotic liver disease (MASLD) in UK biobank - Qi Feng; Chioma N. Izzi-Engbeaya; Pinelopi Manousou; Mark Woodward (BMC Gastroenterology)
Abstract Introduction People with metabolic-dysfunction associated steatotic liver disease (MASLD) had higher risk of extrahepatic multimorbidity, and fibrosis is the strongest prognostic factor for mortality in MASLD. This study aimed to investigate how fibrosis was associated with multimorbidity and their relationships with all-cause mortality. Methods We utilized data from the UK Biobank. MASLD was identified via a Fatty Liver Index ≥ 60 and the presence of cardiometabolic risk factors. The fibrosis-4 (FIB4) score was used to measure liver fibrosis. Multimorbidity was defined as having two or more long-term conditions (LTCs) from a prespecified list of 47 LTCs. Logistic regressions estimated the cross-sectional association between FIB4 scores and multimorbidity prevalence, while Cox models assessed the prospective association between FIB4 scores, multimorbidity and mortality. Results We included 127,470 participants with MASLD (41.7% female, age 57.4 years, 21.3% with multimorbidity, 2.2% with high FIB4 scores). 14,471 deaths were recorded during 13-year follow-up. Compared to low FIB4 scores, high FIB4 scores were associated with 41% higher prevalence of multimorbidity (OR 1.41 (95%CI 1.30–1.54)), and 94% higher all-cause mortality (HR 1.94 (95%CI 1.77–2.13)), while adjusting for multimorbidity reduced the association by 10%, primarily driven by contributions from cardiovascular diseases, extrahepatic cancers, and chronic kidney disease. Conclusion FIB4 scores were positively associated with higher multimorbidity and mortality in MASLD patients. Adjustment for multimorbidity reduced 10% the relationship between fibrosis and mortality, with cardiovascular diseases, cancers and chronic kidney disease contributing notably to this reduction. These findings underscore the importance of managing both fibrosis and multimorbidity in MASLD patients.